KEMAMPUAN BAHASA INDONESIA APARATUR SIPIL NEGARA DALAM KONTEKS PROFESIONALISME BERBAHASA: ANALISIS HASIL UKBI - Kurniawaty, Rahmah; Harjanti, Rina (LPMP Provinsi DKI Jakarta, 2025)
ABSTRACT Proficiency in the Indonesian language is a fundamental competency required of civil servants to support professional communication within governmental institutions. This study aims to analyze the proficiency level of civil servants in using Indonesian in a formal context based on the results of the Indonesian Language Proficiency Test (UKBI). This research employed a quantitative descriptive method with 57 participants from the Educational Quality Assurance Agency (BPMP) of DKI Jakarta Province. The data were obtained from official UKBI results and analyzed using descriptive statistics based on seven levels of language proficiency: Distinguished, Superior, Advanced, Intermediate, Developing, Novice, and Limited. The findings revealed that none of the participants reached the